Algorithms and competition: the latest theory and evidence. Issue 1 (April 2021) - Descamps, Ambroise; Klein, Timo; Shier, Gareth
Abstract : In the modern economy, algorithms influence many aspects of our lives, from how much we pay for groceries and what adverts we see, to the decisions taken by health professionals. As is true with all new technologies, algorithms bring new economic opportunities and make our lives easier, but they also bring new challenges. Indeed, many competition authorities have voiced their concerns that under certain circumstances algorithms may harm consumers, lead to exclusion of some competitors and may even enable firms (knowingly or otherwise) to avoid competitive pressure and collude. In this article, we explain how algorithms work and what potential benefits and harms they bring to competition.